Choosing and using payment instruments: evidence from German microdata - Ulf von Kalckreuth; Tobias Schmidt; Helmut Stix (Deutsche Bundesbank, 2009)
Germans are still very fond of using cash. Of all direct payment transactions, cash accounts for an astounding 82% in terms of number, and for 58% in terms of value. With a new and unique dataset that combines transaction information with survey data on payment behaviour of German consumers, we shed light on how individuals choose payment instruments and why cash remains so important. We propose a two-stage empirical framework which jointly explains credit card ownership and the use of cash. Our results indicate that the pattern of cash usage is compatible with systematic economic decision making. Consumers decide upon the adoption of payment cards and then use available payment media according to their transaction and personal characteristics, the relative costs of cash and card usage, and their assessment of payment instruments' characteristics. Whereas older consumers use significantly more cash, the comparison with younger consumers shows that the difference in payment behaviour is not explained by age as such but to a large extent by differences in the characteristics of these two groups. It is interesting that the possession of a credit card, especially alongside a debit card, does not significantly affect the use of cash in Germany.
Keywords: E41; E58; D12; 330; Payment instruments; payment cards; payment behaviour; payment innovation; cash usage; cash substitution; debit cards; credit cards; survey data; Zahlungsverkehr; Konsumentenverhalten; Kreditkarte; Geldumlauf; Mikrodaten; Deutschland